2017
DOI: 10.1186/s13643-016-0394-2
|View full text |Cite
|
Sign up to set email alerts
|

Are we failing young people not in employment, education or training (NEETs)? A systematic review and meta-analysis of re-engagement interventions

Abstract: BackgroundYouth comprise 40% of the world’s unemployed, a status associated with adverse wellbeing and social, health, and economic costs. This systematic review and meta-analysis review synthesises the literature on the effectiveness of interventions targeting young people not in employment, education, or training (NEET).MethodsRandomised and quasi-randomised trials with a concurrent or counterfactual control group and baseline equivalence are included. Cochrane collaboration tools are used to assess quality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
109
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 19 publications
4
109
0
4
Order By: Relevance
“…Existing policies bear the risk of being more appropriate for those who are work-ready while failing to reach more disadvantaged groups (1). A recent systematic review found limited evidence for effective re-engagement interventions for NEET, and emphasized that existing knowledge is insufficient to guide policy-makers in the planning and implementation of new programs (7).…”
mentioning
confidence: 99%
“…Existing policies bear the risk of being more appropriate for those who are work-ready while failing to reach more disadvantaged groups (1). A recent systematic review found limited evidence for effective re-engagement interventions for NEET, and emphasized that existing knowledge is insufficient to guide policy-makers in the planning and implementation of new programs (7).…”
mentioning
confidence: 99%
“…The term NEET (not engaged in education, employment or training) refers to young people who have dropped out of education, training or work, and who may not register as unemployed as there is little financial incentive to sign on as unemployed 1. Over time, young people who experience NEET-status are at risk of permanent social exclusion 2.…”
Section: Introductionmentioning
confidence: 99%
“…Rightly so, new concepts need to be introduced, questioned and developed 5. NEET-status can be seen as a collective term for including youth who are vulnerable 1. The NEET concept can be a useful tool for targeting means of intervention 9 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using terms such as 'marginal learning' to refer to repeated encounters with employability programmes and other courses focusing on re-engagement, these authors argue that much NEET provision adds to the marginalisation of an already disadvantaged group. Even high-quality interventions have a limited impact (Mawn et al 2017), reminding us of the crucial role of labour markets and training opportunities in the longer-term prospects of NEET young people.…”
Section: Introductionmentioning
confidence: 99%